(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The existence of professional apparatus in various public institutions is still limited, it is necessary to get serious attention to the implementation of government duties and education services can be realized optimally. Based on the problem then the purpose of this research is to know how effectiveness of the implementation of education and training in the leadership of civil state apparatus in the Sangihe Islands District Education Office. This research aims to determine the effectiveness of the development supervision function by the District Education Office of Sangihe Islands. Therefore, in order for this research to know clearly related to the purpose of this research, the authors chose to use a descriptive research method with a qualitative approach. By applying a qualitative approach has a broader opportunity to interact with the research object, so as to enrich and deepen the study in the research the author is doing. The analytical technique used in this research is a qualitative analysis technique which is a research procedure that generates descriptive data in both written and oral words. The approach in this method of analysis is to use interactive analysis The results showed that the implementation of the ASN leadership training in the Sangihe Islands District Education Office can be said to be ineffective because it is not suitable for the purpose that has been established or what is expected. Judging from the timeliness of the implementation of training time so far there are many ASN who are still in line waiting for the turn can be included in training Tepatan time of training by the district and provincial Training agency, making the performance of training body become ineffective. Judging from the benefit dimension of training implementation of ASN ability especially in education environment need to be done evenly and contributed on all ASN in order to increase competence in accordance with standardization teachers will be professional in planning and managing learning process in school. Keywords: effectiveness, education and training, leadership, civil apparatus of the state